Творческое саморазвитие преподавателя как процесс совершенствования его профессионализма - Игнатюк, Ольга Анатольевна (НТУ "ХПИ", 2011)
Статья посвящена проблеме личностно-профессионального развития и совершенствования педагога. В центре внимания исследования находится анализ различных подходов к определению понятия "творческое саморазвитие педагога". В работе приводятся критерии эффективности процесса творческого саморазвития преподавателя.

The article is devoted to a problem of the personal-professional development and perfection of the teacher. At the centre of attention of research there is an analysis of the various approaches to definition of concept creative selfdevelopment of the teacher". In article the criteria of efficiency of process of creative self-development of the teacher are resulted.
Creative self-development of the teacher as process of perfection of his professionalism
Keywords: личностно-профессиональное развитие; самосознание; педагогическое образование; образовательные задачи